Daya tahan mahasiswa angkatan 2025 kelas 35b jurusan PGSD kampus VI UNM bone dalam mengerjakan tugas kuliah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2026)
This study aims to determine the level of resilience or academic resilience of the students in the 2025 cohort, Grade of 35B, Department of Primary School Teacher Education, Campus VI, Universitas Negeri Makassar, in completing assignments for the course Konsep Dasar IPA SD. In this study, academic resilience is focused on students’ ability to maintain their commitment, emotional adaptation, and optimal performance when facing task loads and academic stress, while simultaneously maintaining their mental well‑being during their university years.The research design employed is a quantitative descriptive study using a cross‑sectional survey approach, with a census sample consisting of all students in the class (28 people). Data were collected through a questionnaire measuring seven resilience indicators: accuracy in completing assignments, punctuality in submitting assignments, enthusiasm in doing assignments, completion of assignments according to criteria, creativity in completing assignments, perceived difficulty in completing assignments, and the reasons or awareness underlying the act of doing assignments. Each indicator has a maximum score of 15; the scores were then converted into percentages and analyzed using descriptive statistics.The results show that the average resilience score of students is 12.60, or 84.0% of the maximum score, indicating that, in general, the students demonstrate a “good” to “nearly very good” level of resilience. The highest‑scoring indicator is “reasons or awareness in doing the task” (94.3%), followed by “perceived difficulty in completing the task” (85.0%), suggesting that students are highly aware of the meaning of assignments and do not perceive them as overly heavy. Other indicators such as enthusiasm, completeness, and creativity fall within the range of 82.6–84.0%, while the indicators of accuracy in completing assignments (79.5%) and timeliness in submitting assignments (78.8%) emerged as aspects that still need strengthening. Thus, this study concludes that students in this class possess relatively have strong resilience, but improvements are needed in terms of accuracy and time discipline so that the quality of their learning outcomes and academic work habits become more mature